Validity of Developing PjBL-STEM Based Worksheet on the Topic of Environmental Change and Preservation for Students at MAN 2 Padang Panjang - Iksan, Mila Hidayatul; Fadilah, Muhyiatul (AS-SABIQUN, 2024)
The implementation of the Kurikulum Merdeka requires updated teaching materials that can accommodate suitable learning characteristics. This study is a development research using the 4-D model in three stages: define, design, and develop. The subjects of this study are 35 students from grade X of MAN 2 Padang Panjang, 1 biology subject teacher of MAN 2 Padang Panjang, and two lecturers from the Department of Biology, FMIPA UNP. The object of this research is the PjBL-STEM-based worksheet on environmental change and preservation material. Data for this study are obtained from teacher interviews, student observation questionnaires, and validity questionnaires. The result obtained for the product validity score is 91%, categorized as highly valid, thus can be used in biology learning.